Correlation of ultra-low dose chest CT findings with physiologic measures of asbestosis - Manners, D.; Wong, P.; Murray, C.; Teh, J.; Kwok, Y.; de Klerk, N.; Alfonso, Helman; Franklin, P.; Reid, A.; Musk, A.; Brims, Fraser (2017)
Objectives: The correlation between ultra low dose computed tomography (ULDCT)-detected parenchymal lung changes and pulmonary function abnormalities is not well described. This study aimed to determine the relationship between ULDCT-detected interstitial lung disease (ILD) and measures of pulmonary function in an asbestos-exposed population. Methods: Two thoracic radiologists independently categorised prone ULDCT scans from 143 participants for ILD appearances as absent (score 0), probable (1) or definite (2) without knowledge of asbestos exposure or lung function. Pulmonary function measures included spirometry and diffusing capacity to carbon monoxide (DLCO). Results: Participants were 92% male with a median age of 73.0 years. CT dose index volume was between 0.6 and 1.8 mGy. Probable or definite ILD was reported in 63 (44.1%) participants. Inter-observer agreement was good (k = 0.613, p < 0.001). There was a statistically significant correlation between the ILD score and both forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) (r = -0.17, p = 0.04 and r = -0.20, p = 0.02). There was a strong correlation between ILD score and DLCO (r = -0.34, p < 0.0001). Conclusion: Changes consistent with ILD on ULDCT correlate well with corresponding reductions in gas transfer, similar to standard CT. In asbestos-exposed populations, ULDCT may be adequate to detect radiological changes consistent with asbestosis.